Pedagogical Strategies for Developing the Professional Ethics of Medical Personnel in the Context of Breaking Bad News - Sadovei, Larisa; Postica , Ludmila (Didactica Danubiensis, 2025)
The research objectives refer to highlighting the epistemological dimension of the pedagogical strategy; identifying the particularities of communicating difficult news as a space for manifesting the ethical and emotional competencies of medical staff; determining strategies that facilitate the formation of professional ethics among medical staff for communicating difficult news; establishing methods for curricular integration and assessment of ethical and communication skills among future health professionals. Previous studies present authors' opinions on the role of effective communication in the doctor–patient relationship (Buckman, 1992; Fallowfield, 2009; Ojovanu, 2016); the need to integrate ethics into the medical curriculum (World Medical Association, 2017); the importance of developing emotional and ethical skills for delivering difficult news (Baile et al., 2000; Ptacek & Eberhardt, 1996); the pedagogical dimension of ethics training, based on reflective experiences and clinical simulations (Nestel & Tierney, 2007). The approach to determining pedagogical strategies for training medical professionals in professional ethics in the context of communicating bad news involved scientific synthesis and deduction regarding the correlation between the theoretical foundations of professional ethics and practical exercises in communicating difficult news; curriculum analysis and criteria-based assessment of the skills developed in health students. The research results reflect the identification of a set of pedagogical strategies (Cristea, 2009) applicable in medical ethics training with reference to the communication of difficult news; the importance of experiential learning and clinical simulations for the development of ethical (Gramma, 2025) and communication skills; recommendations for the integration of ethics into the medical curriculum in a cross-cutting and applied manner. The implications refer to the contribution to improving medical training programs by including modules focused on communicating difficult news; strengthening the doctor-patient relationship by increasing the level of empathy and respect; opening up avenues of research on the assessment of ethical skills in medical practice. The value of the research lies in its integrated approach to professional ethics as an ethical, emotional, and pedagogical dimension of medical training and in demonstrating the impact of applying pedagogical strategies on students' progress throughout their studies. A comparative analysis of the results reveals a significant increase in the results of fourth-year students after the application of teaching strategies integrated into the pedagogical strategy for capitalizing on content specific to communicating bad news. This evolution confirms that the strategies applied—problem-based learning, simulations, role-playing, OSCE assessments, and guided reflection—contribute decisively to the development of the professional, ethical, and empathetic conduct necessary for communicating difficult news.